MAKING A BULB KIT PROPERTIES WITH VARIABLE WALLS AS A HEAT TRANSFER LEARNING MEDIA - Raziqi, Gulam Yasir; Yayat, Yayat (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2021)
Teaching about the concepts of conduction and radiation heat transfer in SMK is still difficult for students to understand. The learning process by the teacher has not used the right learning media with the subject being taught. This study aims to increase the understanding of the students of SMK class X TPTU on the subject of conduction and radiation heat transfer through the use of a bulb kit as a learning medium. The method used is quantitative with an experimental research design of one group pretest-posttest design. The respondents involved in this study were 20 students of class X TPTU. The process of validating the bulb kit learning media was carried out by two media experts. The results showed that student learning outcomes have increased by 30%, with a comparison of the average pretest score obtained is 56 with an average posttest score of 86. The use of the bulb kit learning media has made students more active, interested and involved in interacting with the teacher. with a pleasant atmosphere.